Spatial Platform for Periodontal Ligament Angulation and Regeneration: In Vivo Pilot Study - Min Guk Kim; Do-Yeon Kim; Hyoung-Gon Ko; Jin-Seok Byun; Joong-Hyun Kim; Chan Ho Park (Journal of Functional Biomaterials)
The periodontal ligament (PDL) is a fibrous connective tissue that anchors the tooth-root surface to the alveolar bone with specific orientations. It plays a crucial role in functional restoration, optimal position stabilities, biomechanical stress transmission, and appropriate tissue remodeling in response to masticatory loading conditions. This pilot study explored spatial microarchitectures to promote PDL orientations while limiting mineralized tissue formation. A computer-designed perio-complex scaffold was developed with two parts: (1) PDL-guiding architectures with defined surface topography and (2) a bone region with open structures. After SEM analysis of micropatterned topographies on PDL-guiding architectures, perio-complex scaffolds were transplanted into two-wall periodontal defects in the canine mandible. Despite the limited bone formation at the 4-week timepoint, bone parameters in micro-CT quantifications showed statistically significant differences between the no-scaffold and perio-complex scaffold transplantation groups. Histological analyses demonstrated that the PDL-guiding architecture regulated fiber orientations and facilitated the functional restoration of PDL bundles in immunohistochemistry with periostin and decorin (DCN). The perio-complex scaffold exhibited predictable and controlled fibrous tissue alignment with specific angulations, ensuring spatial compartmentalization for PDL tissues and bone regenerations. These findings highlighted that the perio-complex scaffold could serve as an advanced therapeutic approach to contribute periodontal tissue regeneration and functional restoration in tooth-supporting structures.